Correlations of yield and grain yield components of winter wheat varieties - Protić Rade; Todorović Goran; Protić Nada (Journal of Agricultural Sciences (Belgrade), 2009)
Mean positive correlation (r = 0,47**) between grain yield and number of plants per m² and strong correlation between grain yield and number of spikes per m² were established (r = 0,55**). Weak correlation was established between grain yield and productive tillering (r = 0,24**). Strong positive correlation (r = 0,51**) is between the number of spikes per m² and productive tillering, as well as between the number of plants per m² and number of spikes per m² (r = 0,68**). Very weak negative correlation (r = -0,12*) is between productive tillering and the number of plants per m². Regression equations of grain yield and other investigated traits, on the level of significance 5% and 1%, have linear form. By increasing one plant per m², the number of spikes for one per m², productive tillering for one, grain yield will be increased for 0,006 t/ha, 0,005 t/ha and 1,174 t/ha on the average. The other regression equations between the number of spikes per m², number of plants per m² and productive tillering have linear form. By increasing one plant per m² and productive tillering for one, the increase of number of spikes per m² is 1,087 and 312,21 on the average. By increasing the number of plants per m², productive tillering is reduced for 47,59 on the average.